Selecting Embryos with Disabilities? a Different Approach to Defend a “Soft” Paternalism in Reproductive Medicine - Aurenque-Stephan, D (Springer Science and Business Media B.V., 2015)
In this paper I would like to argue that paternalism is sometimes appropriate to promote autonomy. However this is only possible because autonomy and paternalism are not necessarily mutually excluding principles. Contrary to common opinion on this issue, I will show that paternalism can be understood as more than the opposite principle of autonomy. For this purpose, I will present an interpretation of the concept of “paternalism” from Emmanuel Levinas’ understanding of “paternity” with the aim of elucidating the relation between “paternalism” and the concept of autonomy. Finally, I will argue that by accepting a “soft” paternalism in medicine it is possible to make better and more ethically acceptable choices concerning PGD. © 2015, Springer International Publishing Switzerland.